Neurophysiological correlates of interference control and response inhibition processes in children and adolescents engaging in open- and closed-skill sports - Sebastian Ludyga; Manuel Mücke; Christian Andrä; Markus Gerber; Uwe Pühse (Elsevier, 2022)
Background: Accumulating evidence suggests that sports participation promotes the development of inhibitory control, but the influences of the sports category and inhibition type still remain unclear. The categorization of sports based on the open-skill (externally paced) and closed-skill (self-paced) continuum allows for the integration of the environment as a factor contributing to sports-related benefits for inhibitory control. Methods: Cross-sectional data from different studies were combined (n = 184) to examine the association between open- and closed-skill sports and cognitive control processes related to interference control and response inhibition. Participants (aged 9−14 years) filled in 7-day physical activity recall protocols and completed a Stroop Color−Word or a Go/NoGo task. The N200, N450, and P300 components of event-related potentials elicited by these tasks were recorded using electroencephalography. Results: Partial correlations supported the belief that time spent in open-skill sports was related to higher performance on inhibition trials. Additionally, path analyses revealed an association between this sports type and a greater negativity in the N200 and N450 amplitudes in both the full sample and group-level analyses. In contrast, no relation was found between sports type and P300 amplitude. Conclusion: The findings suggest that only the engagement in open-skill sports is associated with more effective conflict monitoring and higher performance on tasks demanding inhibitory control.